USM ALUMNI 1981-1987 INVITED TO ATTEND REUNION GATHERING - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 9 May 2016 All alumni of Universiti Sains Malaysia (USM) who graduated in 1981 1987 are cordially invited to attend a Reunion (RU) gathering to be held on 27 29 May 2016 at the USM campus in Penang.